Stakeholders Reactions to Rebranding of Madiun City: Case Study in Indonesia - Erdiana, Luthfi Widad; Slamet, Slamet (Magister Ilmu Administrasi Publik, 2024)
The Indonesian people have called Madiun City “Kota Brem,” “Kota Pecel,” and “Kota Sepur” since the Dutch era. In line with the Mayor’s leadership policy, the city branding of Madiun was shifted from “Madiun Kota Gadis” to “Madiun Kota Karismatik” and finally to “Madiun Kota Pendekar”. This study examines stakeholders’ reactions to the rebranding of Madiun City. This study uses qualitative research paradigms and case study methods. The primary data sources were obtained through extensive interviews and non-participant observations. Secondary data came from documentation. Data analysis uses Miles and Huberman’s interactive model approach. The study found that the stakeholders are apathetic when responding to the city rebranding due to their low participation and lack of knowledge in the decision-making process. Differences of interest between the government and stakeholders result in a low response.